Increased Perinatal Morbidity and Mortality Among Asian American and Pacific Islander Women in the United States. Issue 4 (December 2017) - Siddiqui, M.; Minhaj, M.; Mueller, A.; Tung, A.; Scavone, B.; Rana, S.; Shahul, S.
Abstract : ( Anesth Analg. 2017;124(3):879–886) Small studies have suggested that there is a difference in obstetric maternal morbidities between Asian American/Pacific Islanders (AAPIs) and Caucasian women, including higher rates of gestational diabetes, peripartum hemorrhage, perineal lacerations, and infections. However, no large nationwide epidemiologic study regarding this issue exists. Therefore, the authors of the present study analyzed data from the National Inpatient Sample (NIS) and compared comorbidities, severe maternal conditions, peripartum complications, and mortality between AAPI and Caucasian women.